Transcriptome Analysis of Dendrobine Biosynthesis in Trichoderma longibrachiatum MD33 - Jia, Qi; Wang, Lina; Qian, Xu; Jin, Hui; Shu, Fuxing; Sarsaiya, Surendra; Jin, Leilei; Chen, Jishuang (Frontiers in Microbiology, 2022)
Dendrobine is a representative component of Dendrobium nobile, and its pharmacological effects have been widely studied. No other sources of dendrobine have been found so far, except isolation from D. nobile and chemical synthesis. Trichoderma longibrachiatum MD33 was isolated from the stem of D. nobile which can produce dendrobine. In order to understand the effect of Methyl Jasmonate(MeJA) on the production of dendrobine , transcriptome analysis was performed on MeJA treatment MD33 and control group. The results showed that MeJA could induce dendrobine accumulation of T. longibrachiatum MD33. When the concentration of MeJA was 20 μ mol/L and the culture time was 15 days, the dendrobine yield in T. longibrachiatum MD33 was the highest (increased 44.6%), but its regulation mechanism was largely unknown. This study was identified by RNA sequencing, a total of 444 DEGs were identified in the control and MeJA treatment groups, including 226 up-regulated genes and 218 down-regulated genes. The Kyoto Encyclopedia of Genes and Genomes annotation showed that a small numbers of DEGs were associated with the putative alkaloid biosynthetic pathway in T. longibrachiatum MD33. The dendrobine is sesquiterpene alkaloids, which are the downstream products of mevalonate (MVA) and methylerythritol 4-phosphate (MEP) pathway. Several MVA pathway enzyme-coding genes (isopentenyl-diphosphate Delta-isomerase, iphosphomevalonate decarboxylase and farnesyl diphosphate synthase) were found to be differentially expressed, suggesting an active precursor supply for the alkaloid biosynthesis under MeJA treatment. A number of MeJA-induced P450 family genes, aminotransferase genes and methyltransferase genes were identified, providing several important candidates to further elucidate the sesquiterpene alkaloid biosynthetic pathway of T. longibrachiatum MD33. Furthermore, many of the MeJA-induced transcript factor encoding genes were identified, suggesting a complex genetic network affecting the sesquiterpene alkaloid metabolism in T. longibrachiatum MD33. Our data aids to reveal the regulation mechanism underlying the MeJA-induced accumulation of sesquiterpene alkaloids in T. longibrachiatum MD33.